Medullary trichomalacia in 6 German shepherd dogs - Tieghi, Chiara (2003)
Medullary trichomalacia is the name proposed for a hair shaft abnormality that was recognized in 6 German shepherd dogs. Affected dogs had multifocal areas of broken hairs, especially on the dorsolateral trunk. Microscopic examination of hair shafts revealed focal areas of loss of architecture, swelling, and apparent softening of the medulla, followed by longitudinal (lengthwise) splitting and breakage of the hair shaft. No cause could be found. Affected dogs were otherwise healthy, and apparent spontaneous recovery was the usual outcome. Relapses may occur.